Annual review of information science and technology. - Cuadra, Carlos A.; American Documentation Institute; American Society for Information Science (New York Interscience Publishers, 1966)
Annual
Issued by the American Documentation Institute.
Keywords: Information science -- Periodicals; Information Science -- Yearbooks; Information storage and retrieval systems -- Periodicals; Libraries -- Automation -- Periodicals